THE EMPOWERMENT OF PONDOKSTAY AS AN ISLAMIC TOURISM DESTINATION POST-COVID-19 - Farahdina Fazial; Sakinatul Raadiyah Abdullah; Surita Hartini Mat Hassan; Salimah Yahaya; Che Khadijah Hamid (Journal of Islamic, Social, Economics and Development, 2023)
Pondok institutions are a form of traditional Islamic educational institutions that have existed since ancient times throughout the Islamic world. Pondok is a place where students learn various disciplines such as religion, Arabic, Fiqh, Tafsir, Hadith, and so on. In the context of Islamic tourism, the lodge institution can be considered as an interesting and unique tourism product to be visited by tourists interested in Islamic culture and history. This matter can indirectly improve the economy of the pondok institution continuously. This is because most pondok institutions in Malaysia are faced with various challenges and constraints to ensure the sustainability of funding. At the federal level, the government has allocated funds of RM 25 million only to registered pondok institutions. However, this situation is seen as not being able to sustain the financial funding of pondok institutions continuously, especially to private pondok institutions. The Covid-19 outbreak has seen lodge institutions also receive a major impact when many lodges are temporarily closed to curb the outbreak. This matter indirectly affects the finances and development of pondok institutions. Therefore, the objective of this paper is to identify the factors that help the establishment of the pondok instituition as an Islamic tourism destination. Second, analyze the potential of pondokstay as an Islamic tourism product in Malaysia. This study uses a bibliographic method consisting of references to journals, articles, books, and theses related to the institution of pondok instituition, pondokstay and Islamic tourism. The results of the study found that development financing in pondok institutions can be implemented through the pondokstay project which aims at Islamic tourism in Malaysia.